Celecoxib is an inhibitor of enzyme acetylcholinesterase - Pohanka, Miroslav (Neuro endocrinology letters, 2016)
OBJECTIVES: Celecoxib is a nonsteroidal anti-inflammatory drug inhibiting enzyme cyclooxygenase-2 (COX-2). The drug was introduced in 1990s. In the work presented here, affinity of celecoxib to enzyme acetylcholinesterase (AChE) is inferred. METHODS: Inhibition of human AChE by celecoxib was tested using standard spectrophotometric Ellman´s method and extrapolation of experimental data by Dixon plot. Interaction between AChE and celecoxib was also predicted by molecular docking using Swiss dock software. RESULTS: A non-competitive mechanism of inhibition was revealed and equilibrium inhibitory constant equal to 313±40 µmol/l was determined. Comparing to AChE, celecoxib was not proved as an inhibitor of enzyme butyrylcholinesterase (BChE). The lowest ΔG was equal to -7.78 kcal/mol. In this case, celecoxib stacked sulfonamide moiety between TYR 337 and TYR 341 of alfa anionic subsite of active site. Cation-Π interactions appears to be responsible for the inhibition. CONCLUSIONS: Though the here revealed and characterized inhibition has lower effect in real conditions than inhibition of COX-2, the inhibitory effect would be utilized in the next research and development of new AChE inhibitors.
Keywords: cholinesterasové inhibitory; Acetylcholinesterase; Dithionitrobenzoic Acid; celekoxib; Molecular Docking Simulation; Cyclooxygenase 2 Inhibitors; Celecoxib; Humans; inhibitory cyklooxygenasy 2; kyselina dithionitrobenzoová; lidé; simulace molekulového dockingu; acetylcholinesterasa; Cholinesterase Inhibitors